Network‐building by community actors to develop capacities for coproduction of health services following reforms: A case study - Susan Usher; Jean‐Louis Denis (Wiley, 2022)
Abstract Introduction Responsive, integrated and sustainable health systems require that communities take an active role in service design and delivery. Much of the current literature focuses on provider‐led initiatives to gain community input, raising concerns about power imbalances inherent in invited forms of participation. This paper provides an alternate view, exploring how, in a period following reforms, community actors forge network alliances to (re)gain legitimacy and capacities to coproduce health services with system providers. Methods A longitudinal case study traced the network‐building efforts over 3 years of a working group formed by citizens and community actors working with seniors, minorities, recent immigrants, youth and people with disabilities. The group came together over concerns about reforms that impacted access to health services and the ability of community groups to mediate access for vulnerable community residents. Data were collected from observation of the group's meetings and activities, documents circulated within and by the group, and semi‐directed interviews. The first stage of analysis used social network mapping to reveal the network development achieved by the working group; a second traced network maturation, based on actor-network theory. Results Network mapping revealed how the working group mobilized existing links and created new links with health system actors to explore access issues. Problematization appeared as an especially important stage in network development in the context of reforms that disrupted existing collaborative relationships and introduced new structures and processes. Conclusion Network‐building strategies enable community actors to enhance their capacity for coproduction. A key contribution lies in the creation of 'organizational infrastructure'. Patient or Public Contribution The lead researcher was embedded over 3 years in the activities of the community groups and community residents. Several group members provided comments on an initial draft of this paper. To preserve the anonymity of the group, their names do not appear in the acknowledgements section.